1997
DOI: 10.1037/0894-4105.11.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Rates of forgetting in organic amnesia following temporal lobe, diencephalic, or frontal lobe lesions.

Abstract: Forgetting rates were examined in patients with diencephalic, temporal lobe, or frontal lesions. No significant differences were found in short-term forgetting of verbal and nonverbal material; in recognition memory for pictures, words, or designs over delays between 1 min and 20 or 30 min; or on a measure of explicit cued recall for words, calculated in terms of the process dissociation procedure. Significantly faster forgetting was found in the diencephalic and the temporal lobe groups in the free recall of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 44 publications
8
50
0
Order By: Relevance
“…Moreover, the pattern of our findings on visuospatial forgetting are consistent with findings in non-epileptic amnesic patients (including those with temporal lobe pathology), which have shown accelerated forgetting within 10 or 20 minutes, after matching for initial memory performance (Christensen et al, 1998;Green & Kopelman, 2002;Isaac & Mayes, 1999a, 1999bKopelman & Stanhope, 1997).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, the pattern of our findings on visuospatial forgetting are consistent with findings in non-epileptic amnesic patients (including those with temporal lobe pathology), which have shown accelerated forgetting within 10 or 20 minutes, after matching for initial memory performance (Christensen et al, 1998;Green & Kopelman, 2002;Isaac & Mayes, 1999a, 1999bKopelman & Stanhope, 1997).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 77%
“…These include: (1) the need to 'match' the starting point from which forgetting is measured; (2) the advantages/disadvantages of different techniques for this matching; (3) avoiding ceiling and floor effects; (4) consideration about whether forgetting should start being measured during or immediately following stimulus presentation; (5) the nature of the distraction activity between test intervals; and (6) whether repeated or equivalent material should be tested at different delay intervals (Brooks & Baddeley, 1976;Green & Kopelman, 2002;Huppert & Piercy, 1977, 1978Isaac & Mayes, 1999a, 1999bKopelman, 1985Kopelman, , 1997Kopelman, , 2000bKopelman & Stanhope, 1997;Mayes, 1988;Mayes & Downes, 1997;McKee & Squire, 1992;Slamecka & McElree, 1983). Reviewing the epilepsy literature, Elliott, Isaac, and Mulhert (2014) published a methodological critique of forgetting studies, which additionally included comments on the need to use both verbal and visual forgetting measures, and the importance of appropriate matching of groups on demographic and cognitive variables.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with glucose and fat, protein was the only macronutrient to influence the rate of forgetting on the paragraph recall test at 15 min; the rate of forgetting is associated with both the medial temporal and diencephalic regions (47). Indeed, after protein ingestion, subjects surprisingly remembered more information during delayed recall than during immediate recall.…”
Section: Discussionmentioning
confidence: 97%
“…According to dualprocess theories of memory, recollection should be affected by certain experimental variables (e.g., levels of processing, divided attention) or subject variables (e.g., aging, brain damage) regardless of whether recollection is indexed using Our finding that free recall has an automatic component also calls into question the experimental strategy of equating free recall performance between groups on initial learning task (e.g., younger and older adults) in order to make sounder inferences. This approach of equating initial learning is often used in neuropsychological studies investigating memory performance between younger and older adults (Giambra & Arenberg, 1993;Harwood & Naylor, 1969;Wheeler, 2000), control subjects and amnesics (Isaac & Mayes, 1999;Kopelman & Stanhope, 1997), older controls and dementia patients (Kopelman, 1985;Reed, Paller, & Mungas, 1998), as well as other subject populations (DeLuca et al, 2004). For example, DeLuca et al found that subjects with chronic fatigue syndrome (and no co-morbid psychiatric disorders) took twice as many trials to learn a list of categorized words to a criterion of two perfect recalls.…”
Section: Implications Of the Finding That Automatic Processes Influenmentioning
confidence: 99%